Cultural Heritage: The Forgotten Resource for Marketing and Sustainable Development of the Local Communities - Vegheș, Călin (European Journal of Sustainable Development, 2019)
Under the slogan “Our heritage: where the past meets the future”, European Union has declared 2018 as the European Year of Cultural Heritage in an unprecedented attempt to enable people to become more interested in and involved with the cultural heritage, and to recognize its universal value and importance in the future development of the individuals, communities and societies. In spite of an increased acknowledgement and extending capitalization, the employment of the cultural heritage, in its tangible and intangible forms, as an asset the local communities may benefit from is still limited. The contribution of the cultural heritage to the sustainable development remains less relevant and illustrates the extent toward which individuals and the local communities, consequently societies, are able to preserve, promote and make the most of this forgotten resource. Paper explores the connections between the cultural heritage, marketing and the sustainable development of the local communities based on the secondary data regarding the involvement, perceived importance, access and participation related to the cultural heritage in order to assess if local communities grasp and consider the potential of this heritage to support their sustainable development through of an appropriate marketing effort. Keywords: Cultural heritage, sustainable development, local communities, marketing